Interaction of Bacillus thuringiensis Cry toxins and the insect midgut with a focus on the silkworm (Bombyx mori) midgut. Issue 1 (2nd January 2020) - Mitsuhashi, Wataru; Miyamoto, Kazuhisa
ABSTRACT: Cry toxins of the bacterium Bacillus thuringiensis (Bt) are used in sprays and the toxin gene-induced crops to suppress insect pests. However, the rapid evolution of Bt Cry toxin resistance in target pests threatens the potency of these agents. There is thus a need to elucidate the mechanism of Bt resistance. Here, we review the relationship between Bt Cry toxins and matrices in the insect midgut, which relates to the mechanism of resistance of insects to Bt. We focus on the interaction between Cry toxins and host ABC transporters in the midgut, which are recognised as important receptors for Cry toxins. We also discuss the role of the midgut peritrophic matrix (PM) in Bt resistance, along with receptors on midgut cells and midgut proteases. The association of the PM with Bt resistance has been little studied. Studies on Bt resistance will improve our understanding of the mode of action of Bt toxins in insects. We consider the contribution of the silkworm Bombyx mori to these studies, since it is widely used in Japan as a model insect for studies of Bt and for sericultural to select for Bt-resistant B. mori larvae.